Pelvic Incidence in Spines With 4 and 6 Lumbar Vertebrae. Issue 7 (October 2019) - Abola, Matthew V.; Teplensky, Jason R.; Cooperman, Daniel R.; Bauer, Jennifer M.; Liu, Raymond W.
Study Design: Anatomical study. Objectives: This study was conducted to determine the prevalence of abnormal lumbar vertebrae (4 and 6) and note any differences in pelvic incidence (PI) between spines with 4, 5, and 6 lumbar vertebrae. Methods: We screened 2980 dry cadaveric specimens from an osteological collection. Pelvises were reconstructed by articulating the sacra and innominate bones. PI was measured in all specimens via lateral photographs. L6-pelvic incidence (L6PI) was also measured, by articulating L6 to the sacrum and measuring PI from the superior aspect of the L6 vertebral body. Results: Of the specimens screened, 969 specimens were evaluated. Average age of death for all specimens was 50.4 ± 15.4 years. The prevalence of 6 lumbar vertebrae was 0.8% (n = 23), and the prevalence of 4 lumbar vertebrae was 1.8% (n = 54). PI measured 38.5° in specimens with 4 lumbar vertebrae, and 46.7° and 47.1° in specimens with 5 and 6 lumbar vertebrae, respectively. PI was significantly different between specimens with 4 and 5 lumbar vertebrae ( P < .001) but not between specimens with 5 and 6 lumbar vertebrae ( P = .38). For specimens with 6 lumbar vertebrae, when L6 was added to the sacrum, mean L6PI was 27.4°. Conclusions: In our large cadaveric study of full spines, we reported a lower prevalence of spines with 4 and 6 lumbar vertebrae compared to previous studies. PI was significantly decreased in subjects with 4 lumbar vertebrae compared with those with normal spines, and special caution should be taken when managing sagittal balance in these patients.